PERENCANAAN FONDASI TIANG PANCANG PADA PROYEK TOWER 2 ARANDRA RESIDENCE - Zulhady Zuhri; Istiatun Istiatun (Construction and Material Journal, 2020)
The pile foundation is an sub-structure to load from the upper structure. Ultimate load carrying-capacity (qu) will be transfered into a hard soil layer by using a deep foundation system. To design the pile foundation, several methods are needed to obtain different bearing capacity values. This study determines the planned pile depth, pile dimensions and pile cap. The purpose of this final project is to plan the pile foundation for the Arandra Residance 2 tower construction project located in Cempaka Putih, Central Jakarta. The method used is the method of Meyerhof, U.S Army Corp, Tomlinson, α and λ. In addition, the calculation of reinforcement, immediate settlement and settlement of primary consolidation was also carried out. The results of the calculation of bearing capacity foundation are different values. The Meyerhof Qu method is 9846,786 kN, the U.S Army Corp method Qu = 11065.11 kN, the Tomlinson Qu method = 10409.68 kN, the method α = 9558.95 kN, and the method λ Qu = 10066.37 kN. Whereas according to Broms, the lateral bearing capacity is 10845 kN. In planning used reinforcement D25-270. Immediate settlement is 50.3 mm, primary consolidation settlement is 9.89 mm, and time rate of consolidation during 1.75 months.  Keywords: Foundation, Driven Pile, Bearing Capacity, Settlement, Primary Consolidation.